(untitled) (Research, Society and Development, 2020)
International market demand for iron ore generates growth in mining industries, increasing the volume of tailings generated, which are deposited in ever-increasing containment dams. However, several accidents involving dams worldwide indicate the need for a mining tailings management plan. Thus, this study aimed to evaluate the spatiotemporal evolution of articles associated with the use of iron mining tailings in civil construction. For this purpose, a qualitative and quantitative documentary research was carried out through the scientific method, which resulted in a sample of 98 articles published between 1960 and 2018. The data obtained indicate an exponential growth of published scientific works, and the countries with the largest number of articles on the theme studied were China (41%), India (11%) and Brazil (9%). The areas of knowledge with the largest number of publications were Engineering with (28.1%), Materials Science (24.1%) and Construction Technology (15.3%). The materials that most commonly used tailings in their composition were concrete, cited in 34 articles and cement, cited in 11 publications. The analysis techniques most cited in the articles were mechanical, chemical, physical and morphological tests. It is noteworthy that the reuse of mining waste in civil construction reduces negative environmental impacts associated with the disposal of these materials, in addition to contributing to the reduction of demand for primary natural resources.